Shc depletion stimulates brown fat activity in vivo and in vitro. Issue 6 (26th September 2014) - Tomilov, Alexey; Bettaieb, Ahmed; Kim, Kyoungmi; Sahdeo, Sunil; Tomilova, Natalia; Lam, Adam; Hagopian, Kevork; Connell, Michelle; Fong, Jennifer; Rowland, Douglas; Griffey, Stephen; Ramsey, Jon; et al.
Summary Adipose tissue is an important metabolic organ that integrates a wide array of homeostatic processes and is crucial for whole‐body insulin sensitivity and energy metabolism. Brown adipose tissue (BAT) is a key thermogenic tissue with a well‐established role in energy expenditure. BAT dissipates energy and protects against both hypothermia and obesity. Thus, BAT stimulation therapy is a rational strategy for the looming pandemic of obesity, whose consequences and comorbidities have a huge impact on the aged. Shc‐deficient mice (ShcKO) were previously shown to be lean, insulin sensitive, and resistant to high‐fat diet and obesity. We investigated the contribution of BAT to this phenotype. Insulin‐dependent BAT glucose uptake was higher in ShcKO mice. Primary ShcKO BAT cells exhibited increased mitochondrial respiration; increased expression of several mitochondrial and lipid‐oxidative enzymes was observed in ShcKO BAT. Levels of brown fat‐specific markers of differentiation, UCP1, PRDM16, ELOVL3, and Cox8b, were higher in ShcKO BAT. In vitro, Shc knockdown in BAT cell line increased insulin sensitivity and metabolic activity. In vivo, pharmacological stimulation of ShcKO BAT resulted in higher energy expenditure. Conversely, pharmacological inhibition of BAT abolished the improved metabolic parameters, that is the increased insulin sensitivity and glucose tolerance of ShcKO mice. Similarly, in vitro Shc knockdown in BAT cell lines increased their expression of UCP1 and metabolic activity. These data suggest increased BAT activity significantly contributes to the improved metabolic phenotype of ShcKO mice.